2020
DOI: 10.1101/2020.10.07.329862
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of hippocampal learning in human infants

Abstract: The hippocampus is essential for human memory. Thus, memory deficiencies in infants are often attributed to hippocampal immaturity. However, the functionality of the infant hippocampus has never been tested directly. Here we report that the human hippocampus is indeed active in infancy. We recorded hippocampal activity using fMRI while awake infants aged 3-24 months viewed sequences of objects. Greater activity was observed when the order of the sequence contained regularities that could be learned compared to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In sum, we found that frontal regions from adult frontoparietal and cingulo-opercular networks are recruited to support stimulus-driven attention in infants. This study adds to the growing evidence that the frontal cortex supports infant cognition, despite undergoing substantial and protracted anatomical development (Ellis et al, 2020a;Raz and Saxe, 2020). Functionality of frontal cortex is honed over the course of development to support complex operations (Munakata et al, 2012), but these regions may be sufficiently developed in infancy to support stimulus-driven attention.…”
Section: Discussionmentioning
confidence: 80%
“…In sum, we found that frontal regions from adult frontoparietal and cingulo-opercular networks are recruited to support stimulus-driven attention in infants. This study adds to the growing evidence that the frontal cortex supports infant cognition, despite undergoing substantial and protracted anatomical development (Ellis et al, 2020a;Raz and Saxe, 2020). Functionality of frontal cortex is honed over the course of development to support complex operations (Munakata et al, 2012), but these regions may be sufficiently developed in infancy to support stimulus-driven attention.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, a mother’s hug that has somatosensory, cardiorespiratory and thermoregulation consequences is accompanied also by her smell, her song and her face [ 35 • ]. Multisensory input about the maternal body is thus bound together in common inferences about the causes of changes to one’s physiological states (embodied mentalisation; [ 12 ]), with this binding possibly being processed by the hippocampus even before episodic memories can be laid down [ 36 ]. In everyday life, feeding, sleeping, bathing routines typically include endless repetitions of multisensory and affect-modulating bundles from at least two bodies.…”
Section: Caregiving Touch As Homeostatic Affect Regulationmentioning
confidence: 99%
“…In adults fundamental research in human and non-human primates has described the nature of the neural representations underlying mature visual categorization abilities, revealing their temporal dynamics 2,9 , what features they encode [10][11][12] , their cortical locus 11,18 , and how they relate to neural oscillations 13,14 . In contrast, these key characteristics of visual category representations [19][20][21][22][23] are less well understood in infants due to strong methodological challenges in human and nonhuman infant neuroimaging research 8,24,25 . In particular, research using EEG -the workhorse of infant neuroimaging for decades -has yielded insights that are principally limited in two ways.…”
Section: Resultsmentioning
confidence: 99%